Grey seal predation impairs recovery of an over‐exploited fish stock. Issue 4 (18th May 2015) - Cook, Robin M.; Holmes, Steven J.; Fryer, Robert J.; Frid, Chris
Summary Grey seal predation has been blamed by fishers for the decline of Atlantic cod stocks and has led to calls for seal culls. In the West of Scotland, estimates of cod consumption by seals have exceeded reported catches and spawning biomass, focussing attention on the interaction between fishers and seals. Bayesian models making different assumptions about seal predation were used to estimate the size of the West of Scotland cod stock between 1985 and 2005 and the mortalities due to fishing and seal foraging. A simple population model was used to identify the likely direction of cod population change at recent mortality rates. All model configurations suggest that the total mortality of cod has remained fairly stable and high for many years regardless of the assumptions on seal predation. The high mortality explains the long‐term decline of the stock. The best‐fitting model suggests that mortality due to fishing reduced substantially in the decade up to 2005, but has been replaced by increased seal predation mortality on a smaller cod stock. Given total mortality estimates, the stock is unlikely to recover even at present reduced levels of fishing. Synthesis and applications. Our model offers a method of estimating seal predation mortality as part of routine stock assessments that inform fishery management. The analysis shows that predation by seals can be an important component of the total stock mortality. It also shows that assuming invariant natural mortality, as adopted in many standard fish stock assessments, may lead to incorrect perceptions of fishing mortality, over‐estimating the benefits of reducing fishing mortality when there is density‐dependent predation. It is essential to consider predation by top predators when formulating appropriate advice for managing the fishery.